Unlocking SARS-CoV-2 detection in low- and middle-income countries - Alcántara, Roberto (2021)
Low- and middle-income countries (LMICs) are significantly affected by SARS-CoV-2, partially due to their limited capacity for local production and implementation of molecular testing. Here, we provide detailed methods and validation of a molecular toolkit that can be readily produced and deployed using laboratory equipment available in LMICs. Our results show that lab-scale production of enzymes and nucleic acids can supply over 50,000 tests per production batch. The optimized one-step RT-PCR coupled to CRISPR-Cas12a-mediated detection showed a limit of detection of 102 ge/μL in a turnaround time of 2 h. The clinical validation indicated an overall sensitivity of 80%–88%, while for middle and high viral load samples (Cq ≤ 31) the sensitivity was 92%–100%. The specificity was 96%–100% regardless of viral load. Furthermore, we show that the toolkit can be used with the mobile laboratory Bento Lab, potentially enabling LMICs to implement detection services in unattended remote regions.